THE IMPACT OF ELECTRONIC DISCLOSURE BASED ON GRI STANDARDS ON ENHANCING THE QUALITY OF ACCOUNTING PROFITS IN THE BANKING SECTOR-AN APPLIED STUDY IN A SAMPLE OF IRAQI BANKS - Sami Latif Jihadi; Nadia Khader AbdelAbbas; Shaima Muhammad (Scholar Express Journals, 2025)
Addressing the theoretical underpinnings of disclosure is the goal of the study. electronic in accordance with the Reporting Global (GRI) Standards Initiative, and describe the impact of it in Increasing the quality of profits Accelerated accounting Activities Look for advancements in science and technology, including those that are compatible with the modern technologies I used during the Deepening Opportunities commerce. Electronically contribute to design knowledge and provide the possibility to send it anywhere in the world. Disclosure In order to meet the demands of Generations New The banks listed on the Iraq Stock Exchange represent the research community in accordance with the demands of the modern business environment. The selection of the research sample was intentional comprising three banks: Bank Credit, Asia, and Iraq Bank and Iraqi Over the course of six years, from 2018 to 2023, the research was implemented in the commercial zone. The study came to several conclusions, the most noteworthy of which was that there was a statistically significant relationship between quality profits and disclosure of information regarding economic, social, and environmental performance as reported by the Standards initiative Reporting Global (GRI). Accounting, that is, the quality of accounting earnings will improve with the degree of electronic disclosure of sustainability in accordance with the standards (GRI).
Keywords: Disclosure Electronic; standards initiative Reporting Global; Quality Profits accounting